Budaya Dagang Tradisional di Era Digitalisasi Perdagangan - Timotius Hernika Putra (Jurnal Riset Akuntansi, 2023)
The field of business of grocery stores or traditional shops is currently experiencing various developments, both the number of shops and the variety of goods they sell is growing. But from the other side, there are also shops that sell their wares not through the physical form of shop buildings, and they take advantage of technological developments, such as the use of smartphones in running their business. Apart from all that, businesses that use online stores can be said to be quite promising because the seller does not need to open a physical store and spend capital to open the store, because now they can still trade only from home and market it through online stores that have been there is this. With this online shop application, there are positive and negative sides, especially if we are dealing with grocery stores that still exist today. Based on what was discussed, the authors used a quantitative research methodology. Based on the results that the author has obtained from these respondents, many of them really like online shopping, both for grocery store needs and personal needs, but there are also respondents who answer that because the emergence of this online shop has actually made their grocery store business sector experienced a decrease in the number of buyers and what most often happened according to these respondents was that the goods that came did not match what was expected.